IS THERE ANY ROOM FOR INNOVATION IN THE MARKETING AUDIT? - Boedi Hartadi Kuslina; Ariesya Aprillia (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
Marketing audit has been evolved since 1950’s to the present. Every decade had its own improvement in its essences, objectives, methods and applications. The audit, however, has many challenges in present and future as it facing different marketing environment, marketing practice and development of other sciences. Some issues have to answer such environmentalism, ethics, change in information technology, culture challenges, strategic management, the use of technology in marketing, value based marketing, multiple products and strategic business units, resource based valuation, scorecards, etc. Marketing audit needs to have some adaptations, could be in the essence, methods and applications. This essay is a literature review regarding marketing audit in the view of methods and applications. The objective of the essay is to stimulate some ideas to innovate the marketing audit.